2001
DOI: 10.1046/j.1365-201x.2001.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation‐induced Ca2+ influx and skeletal muscle cell damage

Abstract: Excessive exercise may lead to skeletal muscle cell damage with degradation of cellular components and leakage of intracellular enzymes. Calcium has repeatedly been proposed to be involved in these processes. Studies have shown that the resting level of cytoplasmic Ca2+ increases up to threefold during long-term low-frequency stimulation. We have shown that electrical stimulation produces a marked increase in Ca2+ uptake and Ca2+ content in rat skeletal muscle, both in vivo and in vitro. Continuous stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 45 publications
1
74
0
6
Order By: Relevance
“…The present observations confirm and extend previous studies (17,20,21) in documenting that Ca 2ϩ gaining access to the cytoplasm from the extracellular phase elicits loss of cellular integrity. The new aspect is that this process seems to be self-increasing, which possibly leads to more extensive muscle damage.…”
Section: Perspectivessupporting
confidence: 82%
“…The present observations confirm and extend previous studies (17,20,21) in documenting that Ca 2ϩ gaining access to the cytoplasm from the extracellular phase elicits loss of cellular integrity. The new aspect is that this process seems to be self-increasing, which possibly leads to more extensive muscle damage.…”
Section: Perspectivessupporting
confidence: 82%
“…This increase in 'leakage' of intramuscular proteins into the bloodstream is just one of the events that are observed following EIMD, which appear as part of the cascade of events following the disruption of the intracellular Ca 2+ homeostasis (Gissel and Clausen, 2001). The increased CRP values, which peaked at 24 h, suggest that the exercise stimulus was also sufficient to elicit an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that eccentric (ECC) contractions induce muscle damage (8,26,44), and it has been suggested that one principal cause of that damage is high [Ca 2ϩ ] i (1,17). Moreover, if ECC does cause increased [Ca 2ϩ ] i , it is possible that stretch-activated ion channels (SAC) are involved in this response (1, 54 -56) and the associated muscle damage.…”
mentioning
confidence: 99%